2006
DOI: 10.1348/135910705x52264
|View full text |Cite
|
Sign up to set email alerts
|

Development of a measure of the concerns held by people with implanted cardioverter defibrillators: The ICDC

Abstract: The questionnaire appears to reflect patients' concerns and, as predicted, these were associated with the patients' anxiety level. The scale requires further testing to reveal if it is of use both clinically and for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…These were identified from consultation with ICD patients, healthcare staff and the research. It targeted the specific ICD concerns that have been shown to lead to increased disability and anxiety and depression,13 and introduced relaxation and better breathing to help patients cope with the “stress” of surgery and ICD implantation. The second booklet explained the best way “to get back to normal and to avoid further problems”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were identified from consultation with ICD patients, healthcare staff and the research. It targeted the specific ICD concerns that have been shown to lead to increased disability and anxiety and depression,13 and introduced relaxation and better breathing to help patients cope with the “stress” of surgery and ICD implantation. The second booklet explained the best way “to get back to normal and to avoid further problems”.…”
Section: Methodsmentioning
confidence: 99%
“…While this attribution of cause allows the ICD patient to make sense of events, the activity is often abandoned or severely curtailed 11. These and other common misconceptions are predictive of anxiety and depression 12 13…”
mentioning
confidence: 99%
“…Device‐related concerns, as perceived by the patient, were assessed with the ICD Concerns (ICDC) questionnaire, which was originally developed in the UK, 15 and later adapted and abbreviated for the Dutch setting 10 . The ICDC consists of eight‐items (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…178 Both of these studies showed no significant change in distress as measured by these instruments. The Patient Concerns Assessment, 164 ICD Concerns Questionnaire, 179 and Florida Patient Acceptance Scale 180 were used in studies that demonstrated that interventions led to significant reductions in concerns/symptoms or significant improvements in acceptance of the ICD. Four studies used the SF-12 181 physical component score as an outcome, with only 1 study demonstrating a significant change using a cardiac rehabilitation intervention.…”
Section: Psychological and Educational Intervention Outcome Measuresmentioning
confidence: 99%